1995
DOI: 10.1002/ana.410370610
|View full text |Cite
|
Sign up to set email alerts
|

Dentatorubral‐pallidoluysian atrophy: Clinical features are closely related to unstable expansions of trinucleotide (CAG) repeat

Abstract: Dentatorubral-pallidoluysian atrophy is an autosomal dominant neurodegenerative disease characterized by various combinations of ataxia, choreoathetosis, myoclonus, epilepsy, and dementia as well as a wide range of ages at onset. A specific unstable trinucleotide repeat expansion in a gene on the short arm of chromosome 12 was recently identified as the pathogenic mutation for this disease. We investigated how the degree of expansion of the CAG repeat effects the clinical manifestations of dentatorubral-pallid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
98
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 27 publications
5
98
2
Order By: Relevance
“…To date, only six families with DRPEA have been reported in non-Japanese populations (Burke et al, 1994;Potter et al, 1995;Warner et al, 1995). In contrast, six families in the Kinki area (this study) and 40 families in other areas of Japan (Ikeuchi et al, 1995;Komure et al, 1995) were positive for the DRPLA repeat expansion. Thus, the DRPLA mutation seems to be common only in the Japanese.…”
Section: Cag Repeat Lengthmentioning
confidence: 49%
“…To date, only six families with DRPEA have been reported in non-Japanese populations (Burke et al, 1994;Potter et al, 1995;Warner et al, 1995). In contrast, six families in the Kinki area (this study) and 40 families in other areas of Japan (Ikeuchi et al, 1995;Komure et al, 1995) were positive for the DRPLA repeat expansion. Thus, the DRPLA mutation seems to be common only in the Japanese.…”
Section: Cag Repeat Lengthmentioning
confidence: 49%
“…ataxia, dementia or mental retardation, myoclonus, epilepsy, choreoathetosis and psychiatric changes including character changes, delusion or hallucinations (Ikeuchi et al, 1995a). We found that ataxia and dementia are cardinal features irrespective of age at onset.…”
Section: Cag Repeat Sizementioning
confidence: 59%
“…patients with no family history of similar cases, has been extremely difficult, since a high penetrance in these diseases makes diagnosis of such cases difficult unless the disease is proven to be transmitted as an autosomal dominant trait. We have so far encountered 6 sporadic cases of DRPLA, in only one of which we had the opportunity to analyze genomic DNA of both parents (Ikeuchi et al, 1995a). The patient had generalized epilepsy at the age of 26, and began exhibiting ataxia and involuntary movements such as choreoathetosis at the age of 37.…”
Section: "Sporadic" Casesmentioning
confidence: 99%
“…A much larger intergenerational increase was observed for paternal transmission (5.8 6 0.9 repeat units/generation) compared to maternal transmission (1.3 6 1.6 repeat units/generation). [5][6][7][8] More prominent genetic anticipation (26-29 years/ generation) due to paternal transmission was revealed, compared to maternal transmission (14-15 years/ generation). 1 If any family member is known to have DRPLA, genetic analysis for the disease could be part of the necessary prenatal testing in pregnancy.…”
mentioning
confidence: 99%